Participation in the Implementation of the Human Right to Water in Tunisia - Tobias Schmitz (Utrecht University School of Law, 2020)
This article analyses the implementation of the human right to water in Tunisia, focusing on the procedural indicator on ‘participation’. The article looks at the functioning of local Water User Associations as the lowest institutional level of water management and reviews theperformance criteria for participation within these associations as applied by the Tunisian government against the background of the legal norms for the human right to water and the indicator on participation within Sustainable Development Goal 6 on water and sanitation, i.e. SDG 6.b.